Bionanomaterial thin film for piezoelectric applications - Ahmad, Farah; Mohd Hatta, Maziati Akmal (Springer, Singapore, 2020)
Wearable and flexible electronics are becoming of recent interest due to expansion of Internet of Things (IOT). Thin film piezoelectric materials have the potential to be used as the development of flexible electronic devices in energy harvesting, sensing and biomedicine. This is mainly be-cause of the inherent ability of piezoelectric materials to convert the mechanical energy to the electrical energy or vice versa. Piezoelectricity in material represents the property of certain crys-talline structure that is capable to developing electricity when pressure is applied. However, con-ventional piezoelectric materials such as PZT (lead zirconate titanate) and PVDF (poly(vinylidene flouride)) are expensive, non-renewable, non-biodegradable and lack of biocom-patibility due to the cytotoxicity nature of lead-based material. Piezoelectric material from natu-ral polymers of biomaterial may provide the solutions for the drawbacks of piezoceramics and piezoelectric polymers. This review emphasis is on the piezoelectricity of various bionanomaterials (cellulose, chitin, chitosan, collagen, amino acid and peptide). The various methods used to measure piezoelectricity of biomaterials is also discussed. This study shows that biomaterials have the potential to be used as piezoelectric nanogenerators in energy harvesting, sensors and biosensors, as well as in cell and tissue engineering, wound healing and drug delivery.